Space and players' number constrains the external and internal load demands in youth futsal - Gomes, Sérgio Adriano; Travassos, Bruno; Ribeiro, João Nuno; Castro, Henrique de Oliveira; Gomes, Leandro Lume; Ferreira, Carlos Ernesto Santos (Frontiers in Sports and Active Living, 2024)
Introduction The aim of this study was to analyze the effects of space and number of players manipulation on the external and internal load demands of youth futsal athletes. Methods Forty-two male U17 players (age = 15.62 ± 0.58 years) from three futsal teams participated in the study. In this cross-sectional study that lasted 8-week, the player's sample practiced six futsal tasks (T1–T6) and a futsal game played under the official rules (T7). From T1–T6, two task constraints were manipulated: (i) the number of players and, (ii) the space of play. The WIMU PRO™ Ultra-Wideband (UWB) tracking system was used to measure the external and internal load during the futsal tasks. External load was quantified using kinematic and mechanical variables extracted from positional data and, the internal load was quantified using Heart rate (HR) and rating of perceived exertion (RPE). Repeated measures ANOVA was used for comparison purposes. Results In general, the results showed high external (total distance, distance 18.1–21, above 21 Km/h, and high intensity acceleration and deceleration, p < 0.001) and internal load (heart rate average and rating of perceived exertion, p < 0.001) in the tasks with low number of players and high area. In relation to the match, the tasks with small relative area per player (GK + 2 vs. 2 + GK and GK + 3 vs. 3 + GK in 20 × 20 m) promoted low external load. Conclusion It was concluded that increasing the relative area by reducing the number of players involved in the tasks in the form of small-sided games (GK + 2 vs. 2 + GK and GK + 3 vs. 3 + GK), in relation to the futsal game (GK + 4 vs. 4 + GK), can be considered a pedagogical strategy to increase the external and internal load demands of young futsal players.